Letter (copy) : Accounts
029-0103-001 LK/555 Finance 19th August, 1937. The Manager, Accounts Department, Co-operative Wholesale Society Ltd. Leman Street, London, E.1. Dear Sir, ACCOUNTS. I shall be glad if you will kindly let me have at your earliest convenience copies of the following invoices: May 4th 17. 9d. May 18th 19. 6d. July 1st £41. 7. 6d. when this matter will receive our attention. Yours sincerely, Finance Department. 292/946/29/103